Penggunaan Kultur Makrofag untuk Pengujian Virulensi Streptococcus equi subs. Zooepidemicus (THE USE OF MACROPHAGE CULTURE IN VIRULENCE ASSAY OF STREPTOCOCCUS EQUI SUBSP. ZOOEPIDEMICUS) - Utama, Iwan Harjono; Pasaribu, Fachriyan Hasmi; Wibawan, I Wayan Teguh; Setiawan, Endhie D. (Jurnal Veteriner, 2016)
Penggunaan Kultur Makrofag untuk Pengujian Virulensi Streptococcus equi subs . Zooepidemicus (THE USE OF MACROPHAGE CULTURE IN VIRULENCE ASSAY OF STREPTOCOCCUS EQUI SUBSP. ZOOEPIDEMICUS)
Keywords: macrophage culture; Streptococcus equi subsp. zooepidemicus